Evaluation of crime watch TV programme. - Chua, Cindy Siew Theng. (2008)
Crime Watch TV programme is a prominent crime prevention programme implemented jointly by Singapore Police Force (SPF) and National Crime Prevention Council (NCPC). It educates the general public about crime prevention and engages the community in fighting crime. This study provides an evaluation on the programme’s effectiveness in preventing crime in partial fulfillment to the final year project required by Nanyang Business School (NBS) under the Home Team Research Grant 2007 awarded by Ministry of Home Affairs (MHA).